Просторові ойконіми українсько-польського пограниччя з гелонімними гідрографічними термінами *lug (*lǫgъ / *lęgъ), luża (< *lougja), :*lǫkъ, *lǫka , *lǫkja, *lǫkavъ,*lǫkavьсь в основі - Редьква, Ярослав Петрович (WN IKiRBL, 2024)
Historical spatial oikonyms of Western Ukrainian and Eastern Polish borderland with gelonym hydrographic terms *lug (*lǫgъ / *lęgъ), luża (< *lougja), :*lǫkъ, *lǫka , *lǫkja, *lǫkavъ,*lǫkavьсь in the stem were analysed in the paper. Within administrative borders of modern Lviv, Ternopil, and Ivano-Frankivsk Oblasts in the western Ukraine and Lublin and Podkarpackie Voivodeships in the east of Poland, etymologies of 33 place names were traced. The place names were of the following type: Залужжя, Залуква, Залуччя, Підлужжя, Налужжя, Залужани (Залужжя), Підлужжя, Dołhołęka, Głęboka Łąka, Łęg, Łąkowe, Łąki Henrykowskie, Łużek, Łączki, Nad Łąkami, Podłąka, Załuże and others. These oikonyms may be reconstructively put into a derivational model: Залужжя // Załuże ≤ *za- + *lǫg- + *-ъje; Залуччя ≤ *za- + *lǫk- + *-ъje, where prefixes за- // za-, на- // na-, під- // pod- perform parallel function to denote spatial characteristics in Ukrainian and Polish oikonymic systems.
Keywords: etymology of place names, historical oikonymy, oikonymic system, Ukrainian-Polish borderland, reconstruction of onyms, toponymics